(untitled) (Research, Society and Development, 2020)
The food industry has shown great interest in the fortification of foods enriched with encapsulated nutritional oils. This work developed linseed oil particles (Linum usitatissimum L.), produced from the ionic gelling technology, using a cat’s claw (Uncaria tomentosa) and barbatimao (Stryphnodendron adstringens) as natural antioxidants. The potential of the antioxidant was evaluated in the control of the oxidative stability of the particulate oil, using the Rancimat equipment. The characterization of the oil obtained from flax seeds indicated a good state of preservation and confirmed a high degree of unsaturation, with the presence of α-linolenic acid (51%). Phenolic profiles of plant extracts showed that 2,5-dihydroxybenzoic as acid and myricetin as flavonoids are the compounds that contribute most to the high antioxidant activity of the vegetal extracts of cat’s claw and barbatimao. From the ionic gelation encapsulation technology, it was possible to obtain a flaxseed oil particle with high encapsulation efficiency. Through oxidative stability curves obtained by the Rancimat equipment concludes that the linseed oil particles expressed greater resistance to oxidation than the fluid oils, demonstrating that encapsulation is a promising alternative to retard the oxidation of oleaginous, combined with the use of natural antioxidants.